Revealing hidden complexities of genomic rearrangements generated with Cas9. Issue 1 (December 2017) - Boroviak, Katharina; Fu, Beiyuan; Yang, Fengtang; Doe, Brendan; Bradley, Allan
Abstract Modelling human diseases caused by large genomic rearrangements has become more accessible since the utilization of CRISPR/Cas9 in mammalian systems. In a previous study, we showed that genomic rearrangements of up to one million base pairs can be generated by direct injection of CRISPR/Cas9 reagents into mouse zygotes. Although these rearrangements are ascertained by junction PCR, we describe here a variety of unanticipated structural changes often involving reintegration of the region demarcated by the gRNAs in the vicinity of the edited locus. We illustrate here some of this diversity detected by high-resolution fibre-FISH and conclude that extensive molecular analysis is required to fully understand the structure of engineered chromosomes generated by Cas9.